Development of organizational structures and programs of participation in the system of agrarian land use - Маркіна, І. А. (Scientific Progress & Innovations, 2017)
A cluster model of dualistic (traditional and organic products) development of land use in Ukraine has been developed. A fundamental difference from existing models is the existence of the National Research and Production Agroecological Park, regional scientific (economic) centers for the development of rural areas and the shift in the emphasis of the role of the state on the realization of economic functions as an agent of land interests. The presented system of information providers in the management of land resources of the agricultural sector of the economy. The concept of development of public-private partnership in the land use system based on agrochemical, meliorative, logistic and marketing directions is offered and aims to ensure the combination of the capabilities of micro-, miniagents, general agents and the state, also with the involvement of regional and global agents, on a complimentary basis for rational land use and increasing the direct and indirect income of all representatives of land interest groups.